1999
DOI: 10.1021/es9808200
|View full text |Cite
|
Sign up to set email alerts
|

Sulfide Controls on Mercury Speciation and Bioavailability to Methylating Bacteria in Sediment Pore Waters

Abstract: A chemical equilibrium model for Hg complexation in sediments with sulfidic pore waters is presented. The purpose of the model was to explain observed relationships between pore water sulfide, dissolved inorganic Hg (HgD), and bulk methylmercury (MeHg) in surficial sediments of two biogeochemically different ecosystems, the Florida Everglades and Patuxent River, MD. The model was constructed to test the hypothesis that the availability of Hg for methylation in sediments is a function of the concentration of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
429
5
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 642 publications
(473 citation statements)
references
References 41 publications
25
429
5
3
Order By: Relevance
“…A limited number of experiments with SRB support this idea (38). For this reason, diffusion across the cell membrane has been proposed as the important uptake mechanism (30,38,74). This hypothesis is consistent with studies that have demonstrated diffusion of neutral mercury complexes (chloride complexes) across artificial membranes and into diatom cells (75)(76)(77).…”
Section: Mercury Speciation and Methylationsupporting
confidence: 76%
See 4 more Smart Citations
“…A limited number of experiments with SRB support this idea (38). For this reason, diffusion across the cell membrane has been proposed as the important uptake mechanism (30,38,74). This hypothesis is consistent with studies that have demonstrated diffusion of neutral mercury complexes (chloride complexes) across artificial membranes and into diatom cells (75)(76)(77).…”
Section: Mercury Speciation and Methylationsupporting
confidence: 76%
“…It has been noted in many field studies that the rate of Hg methylation, and the CH 3 Hg concentration in sediments, decrease as the sediment sulfide concentration increases (28,29,36,37,74,78,79). A number of mercury complexes exist in solution in the presence of dissolved sulfide, including HgSO, Hg(SH)t, Hg(SH)+, HgS;Z· and HgHS z "(80-84) and it is possible that inorganic Hg uptake by SRB occurs via diffusion of the dissolved neutral Hg complexes, such as HgS°.…”
Section: Mercury Speciation and Methylationmentioning
confidence: 99%
See 3 more Smart Citations